2018
DOI: 10.1158/1535-7163.mct-17-0688
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Impact of Nanoparticle Therapy Targeting Tumor-Associated Macrophages

Abstract: Antiangiogenic therapies, despite initial encouragement, have demonstrated a limited benefit in ovarian cancer. Laboratory studies suggest antiangiogenic therapy-induced hypoxia can induce tumor "stemness" as resistance to antiangiogenic therapy develops and limits the therapeutic benefit. Resistance to antiangiogenic therapy and an induction of tumor stemness may be mediated by proangiogenic tumor-associated macrophages (TAM). As such, TAMs have been proposed as a therapeutic target. We demonstrate here that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 46 publications
(60 reference statements)
0
41
0
Order By: Relevance
“…These findings establish a strong rationale for developing TAMs/CCL5 as a novel therapeutic target to inhibit PCSCs and prostate cancer metastasis. Penn et al also used to report that specific elimination of TAMs in murine models of ovarian cancer by TAMs-targeted nanoparticles could significantly decrease the CSCs population and therefore inhibit ovarian cancer growth 41 . Altogether, targeting TAMs may be a promising and powerful strategy to eliminate CSCs which deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings establish a strong rationale for developing TAMs/CCL5 as a novel therapeutic target to inhibit PCSCs and prostate cancer metastasis. Penn et al also used to report that specific elimination of TAMs in murine models of ovarian cancer by TAMs-targeted nanoparticles could significantly decrease the CSCs population and therefore inhibit ovarian cancer growth 41 . Altogether, targeting TAMs may be a promising and powerful strategy to eliminate CSCs which deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In this concept, many approaches have been tested, including the common TIKs that are widely used, but the results are not that promising [91]. Nonetheless, Penn et al demonstrated that blockade of VEGF-C, which is secreted by TAMs, limited lymphagiogenesis and depleted TAMs [92]. As far as TANs are concerned, it was shown that they exert an anti-VEGF function.…”
Section: Mdsc Targeting For Cancer Therapymentioning
confidence: 99%
“…Specifically, Seeger et al showed that the presence of CD177 + neutrophils in colorectal cancer patients is associated with poor prognosis [93]. Finally, blocking of the Ang2/Tie axis was shown to reduce the tumor-promoting functions and recruitment of TAMs [92,94], and could be used as credentials denoting that blocking of secondary angiogenic mechanisms could improve anti-VEGF treatment [93].…”
Section: Mdsc Targeting For Cancer Therapymentioning
confidence: 99%
“…In addition to its role in maintaining organism homeostasis, the immune system also plays a crucial role in the modulation of ovarian function, as it regulates ovarian development, follicular maturation, ovulation and the formation of the corpus luteum [127][128][129][130][131]. In recent years, studies have also shown that immunosuppressive mechanisms and chronic inflammation play an important role in the pathogenesis of ovarian premature aging.…”
Section: Immunosuppressive Mechanisms and Chronic Inflammationmentioning
confidence: 99%